SEMIOTIC REPRESENTATION OF BATAK TOBA WEDDING CEREMONY - Anggi Octorina Nainggolan; Meisuri Meisuri (TRANSFORM : Journal of English Language Teaching and Learning, 2020)
The study is concerned with the way the writer explores the representation of semiotic in Batak Toba Wedding Ceremony, how semiotic is linguistically represented and the reason of semiotic realization as it is. The research method used in this paper is qualitative research which is related to the grounded theory where the sign is described in the culture of Batak Toba based on Pierce’s triadic of semiotic. Pierce’s theory was used in the frame of cultural semiotic representation and focuses on the words, sentences, which was spoken by the speaker in the Video of Wedding Ceremony RN and HS. The interview was assisted by three interviewees who are the speakers in every ceremony of Batak Toba in Medan. The results showed that Semiotic is not only found in a thing. Semiotic also found in a language. The linguistic representation of semiotic will be found in what language that used by a speaker showed the representation of a sign. The classification of verbal and nonverbal helped the writer to find the representation of semiotic linguistically. There were 5 icons, 2 indexes and 3 symbols found in that ceremony.